Karakteristik dan Produktivitas Ayam Kedu Hitam - Achmad Gozali Nataamijaya (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumberdaya Genetik Pertanian, 2008)
The Black Kedu fowl, of Kedu origin district of Temanggung Central Java was one of rare types Indonesian local fowl and considered as productive egg layer amongst local fowls. Therefore, they need to be characterized to better utilize their potential to breed commercial stocks.This study was conducted to find out more reliable data on the characteristics and productivity of the fowl. Two hundred and forty day old chicks were raised in 20 brooders sized 1.5 m x 1.2 m x 0.75 m and fed starter diet contained 20% of crude protein and 3100 kcal metabolizable energy/kg until 4 weeks old, thereafter the birds diet contained 18% crude protein and 3000 kcal metabolizable energy/kg until 8 weeks old then 14% crude protein and 2,800 kcal/kg until 20 weeks old and placed at grower house, after week 20 these hens were removed into layer house. At the age of 21 weeks these birds were given layer diet with 16% crude protein and 2800 kcal metabolizable energy/kg of diet. Drinking water was given ad libitum. Results showed that the dominant plumage colour was shiny black either male or female with red comb and wattle, whilst the colour of shank and beak were mostly dark. The average mortality rate at 1st, 2nd and sixth week was 6.07, 2.16, and 0.43% respectively. The average chicks body weight at day one was 28.98 g. At the 1st to 8th week the average body weight was 40.58, 81.25, 123.60, 192.68, 286.02, 380.39, 487.68, and 578.08 g with feed conversion value of 1.02, 2.58, 2.82, 2.91, 2.98, 3.23, 3.86, and 4.42. Some of the hens started laying eggs at 20 weeks old, however most of them started at 22 weeks old when the production rate was 14.9%. Peak production (41.70%) was reached at 38 weeks old, the average egg production during observation period was 32.48% with feed conversion value for egg production around 6.58. These eggs were laid in the morning (54.36%), the rest were laid in the afternoon (45.64%), the color of the eggs were light brown (75.48%) and brown (25.52%). The average weight of egg was 28.64 g at initial laying period, 35.69 g at peak production and 43.33 g at 52 weeks old, the grade/USDA score of inner egg quality was A/4. It was concluded that the Black Kedu fowl has a distinctive appearance and better productivity compared to ordinary local fowl, and hence could be utilized as genetic resources to develop egg type commercial stock. AbstrakAyam Kedu Hitam, berasal dari Desa Kedu Kabupaten Temanggung Jawa Tengah, adalah salah satu jenis ayam lokal langka dan dikenal sebagai tipe petelur yang cukup produktif. Penelitian bertujuan untuk memperoleh data lengkap karakteristik dan produktivitas ayam Kedu Hitam. Dua ratus empat puluh ekor anak ayam dibesarkan dalam kotak induk buatan berukuran 1,5 m x 1,2 m x 0,75 m dan diberikan pakan starter yang mengandung 20% protein kasar (PK) dan 3100 Kcal/kg energi metabolik (EM) sampai umur 4 minggu, selanjutnya diberikan pakan mengandung 18% PK dan 3000 Kcal/kg EM sampai umur 8 minggu, kemudian pada umur 20 minggu ditempatkan dalam kandang ayam dara serta diberikan pakan dengan 14% PK dan 2800 Kcal/kg EM pada umur 21 minggu ayam dewasa ditempatkan dalam kandang petelur dengan pemberian pakan mengandung 16% PK dan 2800 Kcal/kg EM. Air minum diberikan secara berlebihan. Hasil pengamatan menunjukkan bahwa warna bulu yang dominan adalah hitam berkilauan, baik jantan maupun betina, dengan jengger dan pial berwarna merah, sedangkan sisik kaki dan paruh berwarna gelap kehitaman. Angka kematian pada minggu pertama, kedua, dan keenam 6,07; 2,16; dan 0,43%, rata-rata bobot badan saat menetas 28,98 g, pada minggu pertama sampai minggu ke-8 bobot badan berturut-turut 40,58; 81,25; 123,60; 192,68; 286,02; 380,39; 487,68; dan 578,08 g dengan nilai konversi pakan 1,02; 2,58; 2,82; 2,91; 2,98; 3,23; 3,86; dan 4,42. Ayam betina pada umur 22 minggu telah menghasilkan telur sebanyak 14,9%, puncak produksi (41,70%) pada umur 38 minggu, sedangkan rata-rata produksi telur 32,48% dengan nilai konversi pakan 6,58. Sebanyak 54,36% telur diproduksi pada pagi hari, sedangkan 45,64% pada siang sampai sore hari. Sebagian besar kerabang telur (75,48%) berwarna coklat pucat, sisanya (25,52%) berwarna coklat. Rata-rata bobot telur 28,64 g pada awal masa bertelur, 35,69 g pada puncak produksi, dan 43,33g pada umur 52 minggu, kualitas bagian dalam telur/nilai USDA A/4. Disimpulkan bahwa ayam Kedu Hitam memiliki penampilan yang khas, petelur yang cukup produktif, dan dapat digunakan sebagai sumber daya genetik dalam pembentukan ayam petelur komersial.